9(x+3)=9

Simple and best practice solution for 9(x+3)=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(x+3)=9 equation:


Simplifying
9(x + 3) = 9

Reorder the terms:
9(3 + x) = 9
(3 * 9 + x * 9) = 9
(27 + 9x) = 9

Solving
27 + 9x = 9

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-27' to each side of the equation.
27 + -27 + 9x = 9 + -27

Combine like terms: 27 + -27 = 0
0 + 9x = 9 + -27
9x = 9 + -27

Combine like terms: 9 + -27 = -18
9x = -18

Divide each side by '9'.
x = -2

Simplifying
x = -2

See similar equations:

| 2p^2-12p-14=0 | | 8st-28t-10s-35=0 | | -48=5v+4 | | 3(x-4)=3x-2 | | -63=9s | | K-32+(-16)=-9 | | 8=5p+13 | | 15=2x-7 | | m(1.50)+5=15.50 | | -1.7+H=-2.2-3.4 | | 3n-3=-15-5n | | x^2+4=4n | | -96/4=4c/4 | | 4x+14+10x= | | -19h+19h+-3h=-18 | | -5=(-2b) | | 3x^8-18x^6=0 | | 5t+11=7t-13 | | 2x-16=3x-12 | | -2y-6=-10 | | F-(-40)=-12 | | 6a/6=0.96/6 | | 5(m-3)+2m=2 | | x+9=1.5 | | (7+2i)+(1-4i)=0 | | x^2=-2x-3x | | .37+1.1x=2.65x-1.18 | | 12=3(p+2) | | 3n-6=-15 | | -.8x=10 | | 5x^2+3x-21=6-3x | | 40-4x=1x |

Equations solver categories